2016
DOI: 10.7554/elife.17636
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA switch mediates the dynamic control of flavivirus replicase recruitment by genome cyclization

Abstract: Viral replicase recruitment and long-range RNA interactions are essential for RNA virus replication, yet the mechanism of their interplay remains elusive. Flaviviruses include numerous important human pathogens, e.g., dengue virus (DENV) and Zika virus (ZIKV). Here, we revealed a highly conserved, conformation-tunable cis-acting element named 5′-UAR-flanking stem (UFS) in the flavivirus genomic 5′ terminus. We demonstrated that the UFS was critical for efficient NS5 recruitment and viral RNA synthesis in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 76 publications
8
85
0
Order By: Relevance
“…cis-Acting RNA elements are involved not only in viral replication (35,36,41,(44)(45)(46)54) and translation (55,56) of flaviviruses but also in host adaption (57), neurovirulence (58), and pathogenicity (59)(60)(61). Using the ZIKV replicon and the newly developed infectious clone of ZIKV, we have shown that 5=-SLA and 5=-3= CS interaction are indispensable for ZIKV replication.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…cis-Acting RNA elements are involved not only in viral replication (35,36,41,(44)(45)(46)54) and translation (55,56) of flaviviruses but also in host adaption (57), neurovirulence (58), and pathogenicity (59)(60)(61). Using the ZIKV replicon and the newly developed infectious clone of ZIKV, we have shown that 5=-SLA and 5=-3= CS interaction are indispensable for ZIKV replication.…”
Section: Discussionmentioning
confidence: 97%
“…It was also showed that the 5=-SLA and 5=-3= CS base-pairing restoration mutants consistently replicated moderately lower than the WT, suggesting that tertiary or quaternary interactions may be involved in the functionalization of these cis-acting RNA elements. Previously, studies suggested that the conserved UFS element is required for ZIKV replication (45) and that the SL-I/xrRNA1 structure is responsible for the production of ZIKV sfRNA (62). Thus, the RNA-based regulation mechanism of ZIKV should be highly similar to other well-studied mosquitoborne flaviviruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…99 Recently, Liu et al (2016) identified a conserved RNA switch, the 5′-UAR-flanking stem (UFS), which extends the SLB structure and enhances recruitment of NS5 and RNA synthesis. 101 …”
Section: Biochemistry and Molecular Biology Of Flavivirusesmentioning
confidence: 99%